Cell surface Toll-like receptor polymorphisms influence Bartonella and ectoparasite infections in striped hamsters - Xinchang Lun; Yujuan Yue; Yiguan Wang; Guichang Li; Ning Zhao; Fengxia Meng; Qiyong Liu; Pengbo Liu; Zihao Wang; Zhenxu Wang; Xiuping Song; Jun Wang; et al. (iScience, 2025)
Summary: This study explored how polymorphisms in cell surface Toll-like receptors (TLRs) influence susceptibility to Bartonella and ectoparasite infections in striped hamsters. Among six TLR genes, four sites in TLR1, TLR4, and TLR10 genes were associated with Bartonella susceptibility, while twelve sites across TLR4, TLR5, and TLR10 contributed to flea resistance. Similarly, eleven sites in TLR5, TLR6, and TLR10 were linked to gamasid mite parasitism. Genetic polymorphism analysis revealed that when heterozygous or rare genotypes protected the host from infections, the polymorphisms of these sites in uninfected individuals exceeded that of the infected group. The distribution of these sites on the three-dimensional structure of TLRs varied. All Bartonella-related sites were in the extracellular domain, whereas some of those related to fleas and gamasid mites were located in other domains. This research highlights the importance of cell surface TLRs in immune regulation and provides insights into evolutionary dynamics in natural environments.